1999
DOI: 10.1007/s002130050996
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic demand for alcohol in rats

Abstract: Rats defended baseline alcohol consumption but not baseline food consumption. As alcohol and food consumption can be dissociated in humans, research on the mechanisms that mediate alcohol regulated preference in rats may shed light on the mechanisms that control human alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
0
10
1
2
Order By: Relevance
“…In contrast, in the present study, increasing the response requirement during the seeking component did not alter drinking behavior once access to alcohol was obtained, with intake remaining relatively constant. Studies using a variety of procedures and a variety of species [rats: (Heyman, 1997;Heyman et al, 1999;Petry and Heyman, 1995;Williams and Woods, 2000), rhesus monkeys: (Carroll et al, 2000), humans: (Goudie et al, 2007;Sumnall et al, 2004)] have also demonstrated that alcohol intake is resistant to change, in that subjects will defend their alcohol intake despite large increases in response cost. That is, in economic terms, alcohol can be considered an ''inelastic'' commodity (Heyman, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, in the present study, increasing the response requirement during the seeking component did not alter drinking behavior once access to alcohol was obtained, with intake remaining relatively constant. Studies using a variety of procedures and a variety of species [rats: (Heyman, 1997;Heyman et al, 1999;Petry and Heyman, 1995;Williams and Woods, 2000), rhesus monkeys: (Carroll et al, 2000), humans: (Goudie et al, 2007;Sumnall et al, 2004)] have also demonstrated that alcohol intake is resistant to change, in that subjects will defend their alcohol intake despite large increases in response cost. That is, in economic terms, alcohol can be considered an ''inelastic'' commodity (Heyman, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…As with the consumption of nondrug reinforcers, the consumption of drugs (eg ethanol, phencyclidine, cocaine, heroin) decreases in the face of increasing prices in both rats (eg Comer et al, 1996;Solinas et al, 2004;Heyman et al, 1999) and monkeys (Carroll et al, 1991;Carroll, 1996, 1997;Ko et al, 2002) (for a general review, Bickel et al, 1995). In the majority of studies, the demand for drug is initially inelastic to changes in price and then becomes elastic above a certain price, called P max (Hursh, 1991;Bickel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The average intakes in the current experiments were close to 1 g/kg in an out-bred strain of rats that had free access to food and water in the home cage. Although one may argue that the rats consumed the solution due to the enhanced palatability rather than ethanol’s pharmacological effects, studies using a behavioral economics approach show otherwise (Heyman, 1997; Heyman et al, 1999). In experiments in which rats had a choice between an alcohol/saccharin solution and a sweet solution of equal calories, the rats allocated their responses toward the alcohol solution as response requirements increased even if the alcohol solution was the non-preferred solution under baseline conditions (for review, see Heyman, 2000).…”
Section: Introductionmentioning
confidence: 99%